PERGESERAN BAHASA DAERAH LAMPUNG PADA MASYARAKAT KOTA BANDAR LAMPUNG - Nandita Wana Putri (Universitas Sebelas Maret, 2018)
Lampung is one of the provinces in Indonesia which is located strategically. It is located at the Southern of Sumatra Island that makes Lampung as the only gateway for those who want to go to Sumatra Island. The complexity of the society in Lampung, especially in Bandar Lampung city, has an impact on the survival of indigenous people of Lampung itself. One of the effects is the waning of the indigenous languages of Lampung in the city. The aim of this study is to find out the reasons why Lampung is starting to be abandoned, to know how to use Lampung Language, to know what areas still survive in the use of Lampung Language, and to describe what efforts have been made to preserve the Lampung language in the Bandar Lampung city. The qualitative approach is used in this study. The data are obtained by applying the methods of observation, interview and document analysis. This study found that in Bandar Lampung city Lampung language experience a language shift which then will be extinction if not preserved optimally.